Physical exercise elicits UPRmt in the skeletal muscle: The role of c-Jun N-terminal kinase - Rodrigo Stellzer Gaspar; Carlos Kiyoshi Katashima; Barbara Moreira Crisol; Fernanda Silva Carneiro; Igor Sampaio; Leonardo dos Reis Silveira; Adelino Sanchez Ramos da Silva; Dennys Esper Cintra; José Rodrigo Pauli; Eduardo Rochete Ropelle (Elsevier, 2023)
Objective: The mitochondrial unfolded protein response (UPRmt) is an adaptive cellular response to stress to ensure mitochondrial proteostasis and function. Here we explore the capacity of physical exercise to induce UPRmt in the skeletal muscle. Methods: Therefore, we combined mouse models of exercise (swimming and treadmill running), pharmacological intervention, and bioinformatics analyses. Results: Firstly, RNA sequencing and Western blotting analysis revealed that an acute aerobic session stimulated several mitostress-related genes and protein content in muscle, including the UPRmt markers. Conversely, using a large panel of isogenic strains of BXD mice, we identified that BXD73a and 73b strains displayed low levels of several UPRmt-related genes in the skeletal muscle, and this genotypic feature was accompanied by body weight gain, lower locomotor activity, and aerobic capacity. Finally, we identified that c-Jun N-terminal kinase (JNK) activation was critical in exercise-induced UPRmt in the skeletal muscle since pharmacological JNK pathway inhibition blunted exercise-induced UPRmt markers in mice muscle. Conclusion: Our findings provide new insights into how exercise triggers mitostress signals toward the oxidative capacity in the skeletal muscle.